Wyposażenie pojezuickiego kościoła św. Franciszka Ksawerego w Grudziądzu jako przykład maniery chinoiserie - Kowalczyk, Justyna (Sztuka i Kultura, 2021)
The equipment of St. Franciszek Ksawery church in Grudziądz determines the unique character of that church in Poland. It presents rich regent style with numerous elements of the decoration which was fashionable especially in the beginning of 18th century and imitated the art of China, namely chinoiserie. Chinoiserie decorations, popular in Polish secular art, can also be found in sacral interiors. Initially, they made their way into churches as gifts of wealthy founders, however, in the case of Jesuit churches they became a conscious concept. Chinoiserie in the interiors of Jesuit churches constituted not only the reflection of their missionary activity but also a conclusion to multiple research and writings on China and Japan as well as other Asian countries. It brought along a completely new iconography and ideology, which we can find in such large numbers in the Grudziądz church. We can notice it starting from the main altar, where on particular items there are decorations realized in the imitation of black lacquer, depicting exotic landscapes full of oriental animals and plants (parrots and palms). Black lacquer can also be found in the decoration of the pulpit. There, among exotic landscapes there are individual apostles as well as saints, and similarly as in the confessionals, the attributes of individual saints were entwined into chinoiserie decorations. The quintessence of the employment of Chinese varnish remains in the music choir, whose three panneaus depict the scenes of the Jesuits’ missionary road in Asia among exotic plants. Even the side altars, although not embellished with black lacquer, refer to the program, in particular the south altar devoted to St. Ignacy Loyola in the surrounding of four continents. The employment of chinoiserie in church decoration had never been used in such a scale in a sacral building – an exception to which can be the already non-existent convent church in Międzyrzecze (its equipment partially preserved in Wyszanów), where the same artists might have worked. In some Polish churches there are single pieces decorated in this way, sometimes a few, like in Studzian. The subject matter of chinoiserie in Polish sacral art still largely remains insufficiently examined and described. Therefore, there is hope for further discoveries in the area.